Development of Learning Media at Junior High School: Comic Reading Applications Using Software Ispring Suite - Gombah, Wimansya; Ismail, Sumarno; Pauweni, Khardiyawan (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The background research was conducted as an effort to overcome students' low interest and understanding of mathematics due to the monotonous learning approach. Therefore, this study aims to develop a mathematics learning media application in the form of comics that focuses on the material of linear equations with two variables, specifically designed for eighth-grade junior high school students. This research uses the Plomp development model, which includes the stages of initial investigation, design, realization/reconstruction, test, evaluation and revision, and implementation. This research was conducted at Junior High School 1 Bulango Timur. The data collection approach used in this research is a validation sheet and a questionnaire for students and teachers. Data analysis in this study used qualitative descriptive analysis. The results of validation by experts show that this media is valid, with the readability test obtaining a feasibility level of 97.27% and student responses reaching 99.2% (very practical). Teacher responses also showed practicality at 91.7%. This media is proven to increase student learning motivation, facilitate understanding of abstract concepts, and create captivating learning experiences, so it is feasible to be applied in learning mathematics on the material of the system of linear equations of two variables.